2022
DOI: 10.1111/acer.14883
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects of alcohol in adults with chronic jaw pain

Abstract: Background Although recent literature provides promising support for the analgesic properties of alcohol, potential differences in alcohol analgesia as a function of chronic pain status are not well understood. Thus, this study examined chronic pain status as a potential moderator of alcohol analgesia and distinguished between multiple aspects of pain experience and sensitivity: pain threshold, pain intensity, pain unpleasantness, and perceived relief. Methods Social drinkers with (N = 19) and without (N = 29)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Although greater pain threshold ( p < .0001, η p 2 = .21) and lower pain intensity ( p = .04, η p 2 = .10) were reported in the alcohol than placebo condition (Vitus et al, 2022), bivariate correlation analyses (Pearson’s r ) demonstrated that alcohol-induced changes in pain threshold and pain intensity were not significantly correlated with relief ratings ( p > .49).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Although greater pain threshold ( p < .0001, η p 2 = .21) and lower pain intensity ( p = .04, η p 2 = .10) were reported in the alcohol than placebo condition (Vitus et al, 2022), bivariate correlation analyses (Pearson’s r ) demonstrated that alcohol-induced changes in pain threshold and pain intensity were not significantly correlated with relief ratings ( p > .49).…”
Section: Resultsmentioning
confidence: 96%
“…However, the expectancy that alcohol reduces pain sensitivity (AE VAS 2) was not significantly associated with perceived pain relief regardless of chronic pain status. In addition, alcohol-induced increases in pain threshold and reduction in pain intensity (Vitus et al, 2022) were not correlated with perceived pain relief. This finding provides additional evidence that alcohol-induced changes in pain sensitivity may not completely explain perceived pain relief (Edwards & Fillingim, 2007; Leknes et al, 2013), and thus may fail to sufficiently characterize the negative reinforcing effects of alcohol use for pain self-management.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A valuable meta-analysis constructed a dose-effect curve for alcohol analgesia in human subjects (Thompson et al, 2017) while issuing the warning that alcohol use near or above binge drinking levels is typically required for effective pain relief. An important recent study (Vitus et al, 2022) examined alcohol analgesia in chronic jaw pain sufferers at this exposure level (around 0.08 g/dl), which also corresponds to the legal driving limit in several jurisdictions. The major research question explored was whether the efficacy of alcohol to relieve pain might be altered in individuals with a history of chronic pain.…”
Section: Chronic Pain Affects Over 100 Million Individuals In the Unitedmentioning
confidence: 99%